The Influence of Financial Compensation on the Performance of Daily Workers at the Laguna Resort and Spa Nusa Dua, Bali - Irene Hanna H. Sihombing; I Wayan Yudha Pangestu (Jurnal Multidisiplin Madani, 2023)
The development of regulations, policies and strategies applied by The Laguna Resort and Spa Nusa Dua, Bali by providing additional financial compensation in the form of service charges to daily workers which are not applied by hotels in general.  The assessment of this decision is certainly important to determine the effect of financial compensation on the performance of the daily workers. This study successfully identified and observed items of financial compensation that affect the performance of daily workers, namely related to the fulfillment of basic wages, adjustment of basic wages, provision of service charges, safety benefits and provision of adequate work tools. Financial compensation has a positive and significant effect with a value of 53.3% on the performance of the daily workers, where the service charge is the most influential item of financial compensation in improving performance. Meanwhile, the increase in work productivity shown through the level of attendance at work every month is the highest item affected by financial compensation.  In addition, the increase in daily worker performance is also influenced by other variables not examined in this study